The development of a scientific attitude inventory test a research instrument designed to assess and measure changes in scientific attitudes of high school physics teachers - Formacion, Sonia P. 1940- ([Quezon City s.n.], 1973)
This paper proposed the construction of a set of inquiry slides for teaching ecology in the elementary grades. It includes a description of the procedure used in the construction of the slides, the set of slides constructed and the teaching strategy that may appropriately be used with the slides.
Thesis (M.A.T.)--University of the Philippines.
Typescript (carbon copy).
Keywords: Science teachers -- Philippines